PENGARUH PIJAT PERINEUM TERHADAP TINGKAT KECEMASAN PADA IBU HAMIL PRIMIGRAVIDA TRIMESTER III - Dwi Masita, Elly (Jurnal Ilmiah Kesehatan, 2016)
Physical changes and psychology in pregnancy is one stressor in pregnancy. Preliminary studies showed that 98% of pregnant women experience anxiety third trimester. As a result of the pregnancy is maternal anxiety will experience periods of abnormal labor so as to improve maternal and infant mortality. Objective: This study aimed to determine the effect of perineal massage in primiparous mothers anxiety in the third trimester to the third trimester pregnant women in the BPS. Istiqomah, S.Keb.Bid. Methods: This research is pre-experimental design with a population statistical comparison group of pregnant women in the third trimester of BPS. Istiqomah. S.Keb.Bid premises sample of 20 pregnant women were divided into 10 groups of 10 samples of treated and control groups. Sampling nonprobality sample with quota sampling technique. The instrument of this study using a questionnaire anxiety. Results: Of the 10 treatment group gained 9 (90%) of the study subjects experienced a lower level of anxiety while the control group of 10 4 (40%) of research subjects experienced lower levels of anxiety and test results Mann - Whitney was obtained p = 0.005 (p < 0.05), which means there is perineal massage effect on the level of anxiety in the third trimester pregnant women. Conclusion: There is the effect of perineal massage on the level of anxiety in the third trimester pregnant women with p = 0.005